GAMBARAN PERSEPSI STRES AKADEMIK PADA PROSES PEMBELAJARAN MAHASISWA TAHUN PERTAMA DI FAKULTAS KEPERAWATAN UNIVERSITAS RIAU - Melati Sukma; Darwin Karim; Siti Rahmalia Hairani Damanik (Universitas Karya Husada Semarang, 2025)
Introduction: Academic stress occurs when academic demands are perceived as exceeding individual capacity. Objective: This study aims to describe the perception of academic stress in students covering the first year of Riau University. Method: This descriptive quantitative study used a cross-sectional approach. Data were collected using the Perception of Academic Stress Scale (PASS) questionnaire, which includes 18 validated and reliable items. The sample consisted of 160 first-year students from four classes, selected through stratified random sampling. Univariate analysis described respondent characteristics and stress levels. Results: Most respondents were late teens (91.3%), female (92.5%), entered via SNBT (36.9%), and experienced moderate stress levels (78.1%). For academic expectations (69.4%), for workload and exams (77.5%), and for academic self-perception (69.4%). Conclusion: Most first-year nursing students at Riau University experience moderate academic stress. Future research should consider additional factors such as parenting style, emotional intelligence, and self-confidence to inform effective interventions.